4D BIM integrated construction supply chain logistics to optimise on-site production. Issue 12 (10th September 2022) - Magill, Leslie J.; Jafarifar, Naeimeh; Watson, Alan; Omotayo, Temitope
Abstract: Loss of productivity through on-site delays and disruptions is a significant problem in the construction industry. This can be caused by workforce, materials, and equipment clashes. A major need for the industry is to improve construction logistic efficiencies for materials and equipment from manufacture to the point of use by the workforce. The authors investigate the effectiveness and efficiency of integrated construction supply chain logistics (ICSCL) using 4D Building Information Models (BIM), via three information streams: literature, a case study of the Elephant and Castle project (E&C), and a survey from UK construction professionals. The results illustrate, although BIM of various levels is currently in use throughout the UK, 4D BIM for ICSCL is not extensively utilized due to an absence of strategy, perceived costs of IT, and training requirements. That use could potentially add value with a trusted supply chain and disciplined planning using a multiple stream logistic model.